Laboratory‐developed contact models controlling instability on frictional faults. Issue 6 (2nd June 2015) - Selvadurai, Paul A.; Glaser, Steven D.
Abstract Laboratory experiments were performed on a polymethyl methacrylate (PMMA)‐PMMA frictional interface in a direct shear apparatus in order to gain understanding of fault dynamics leading to gross rupture. Actual asperity sizes and locations along the interface were characterized using a pressure‐sensitive film. Slow aseismic slip accumulated nonuniformly along the fault and showed dependency on the applied normal force—increased normal force resulted in higher slip gradients. The slow slip front propagated from the trailing (pushed) edge into a region of more densely distributed asperities at rates between 1 and 9.5 mm/s. Foreshocks were detected and displayed impulsive signals with source radii ranging between 0.21 and 1.09 mm; measurements made using the pressure‐sensitive film were between 0.05 and 1.2 mm. The spatiotemporal clustering of foreshocks and their relation to the elastodynamic energy released was dependent on the normal force. In the region where foreshocks occurred, qualitative optical measurements of the asperities along the interface were used to visualize dynamic changes occurring during the slow slip phase. To better understand the nucleation process, a quasi‐static asperity finite element (FE) model was developed and focused in the region where foreshocks clustered. The FE model consisted of 172 asperities, located and sized based on pressure‐sensitive film measurements. The numerical model provides a plausible explanation as to why foreshocks cluster in space and observed a normal force dependency and lend credence to Ohnaka's nucleation model.